Hubungan Kegiatan Keagamaan dengan Pembentukan Karakter Religius Siswa Kelas VIII - Latifah, Maimunatul; Srinarwati, Dwi Retnani; Zaman, Akhmad Qomaru; Suyono, Suyono; Suhartono, Suhartono (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2026)
This study aimed to describe the implementation of religious activities, identify the level of religious character, and examine the relationship between both variables among eighth-grade students at SMP Negeri 16 Gresik. The study used a quantitative correlational design. The population consisted of 295 students, and 75 students were selected through proportionate random sampling. Data were collected using Likert-scale questionnaires on religious activities and students' religious character. Data analysis employed descriptive statistics, normality and linearity tests, Pearson Product Moment correlation, and coefficient of determination. The results show that religious activities were in the high category (M = 61.46), while students' religious character was also high (M = 61.00). The prerequisite tests confirmed normal distribution and linear relationship. Hypothesis testing revealed a positive and significant relationship between religious activities and students' religious character (r = 0.612; p < 0.05). Religious activities contributed 37.4% to the formation of religious character. These findings indicate that systematic school religious programs support the internalization of religious values in students' daily lives.